Hungarian Monitoring, 8 March 1990 . [Magyar rádiófigyelő], 1990. március 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR: national unity, Lithuanian secession, Romanian foreign minister's talks, communist opposition, Lenin statue pulled down in Tbilisi, women's protests - Split expected in Solidarity - Latest political scandals and denials in the GDR - Last days of the Italian CP Domestic Affairs: - Soviet troop withdrawals - Gabčíkovo-Nagymaros dam - Parliament's Property Accounting Committee commences its hearings - Taking up Hungarian citizenship to be simplified - Health checks in Tengiz and Hungary - Elections: party meetings, press conference, vote-counting system, election consultancy - Allocating responsibility for past mistakes - Open letter to György Marosán Economy: - EFTA membership Külpolitika: - SZU: német egység, Litvánia kiválása, a román külügyminiszter tárgyalásai, kommunista ellenesség, Lenin szobor döntés Tbilisziben, nők tüntetése - Szakadás várható a Szolidaritásban - Újabb politikai botrány és cáfolat az NDK-ban - Az olasz KP végnapjai Belpolitika: - Szovjet csapatkivonás - Bős-Nagymaros vízlépcső ügy - Megkezdte meghallgatásait a Parlament Vagyonelszámoltató Bizottsága, - Egyszerűsödik a magyar állampolgárság felvétele - Egészségügyi ellenőrzés Tengizben és Magyarországon - Választás: pártok gyűlése, sajtótájékoztatója, szavazatszámláló rendszer, választási tanácsadó - A múlt hibái miatti felelősségre vonás kérdése - Nyílt levél Marosán Györgyhöz Gazdaság: - EFTA tagság